P393 Long-term prediction of infliximab response using CD-62L shedding assay: Longitudinal data from 5-year study in inflammatory bowel disease. (16th January 2018) - Macpherson, J; Bravo, F; Andrew, P; Slack, E; Patuto, N; Cahenzli, J; McCoy, K D; Macpherson, A J; Juillerat, P
Abstract: Background: The mechanism of loss of response of anti-tumour necrosis factor alpha (TNFα) agents in inflammatory bowel disease (IBD) patients is poorly understood and long-term prognostic markers of therapeutic efficacy are required for ensuring successful clinical treatment. Methods: An in vitro blood assay was developed to predict patient response to the anti-TNFα agent infliximab. Crohn's disease (CD) and ulcerative colitis (UC) patients were then classified according to the shedding of an L-selectin (CD62L) from the surface of granulocytes in whole- blood. CD62L shedding was quantified by flow cytometry before and after infliximab administration. A 5-year (June 2015 to August 2017), prospective clinical study, comprised of blinded infliximab management, hospitalisation, complication and surgery, was aimed at validating the long-term predictive value of this test. Results: We identified 62 patients eligible for the study over a 2-month cycle of infliximab maintenance therapy at our infusion centre at Bern University Hospital. 33 IBD patients, who consented to the study with at least one valid testing (fresh blood), were included. According to the in vitro test, 22 (17 CD and 5 UC) were predicted as responders (PR) and whereas 11 (8 CD and 3 UC) were predicted as non-responders (NR). Five years after study initiation, 72% of PR were still treated with infliximab (suggesting a stable response to infliximab treatment), whereas only 27% of NR remained on treatment ( p < 0.05), respectively. The median time spent under Infliximab therapy after CD62L shedding quantification was 45 (IQR 34.25–48.5) and 12 (IQR 3.5–35) months ( p = 0.019), in PR and NR respectively. Seven patients (4 in the PR and 3 in the NR group) were lost to follow-up. Thirty-five medico-surgical events occurred, 70% during the first 3 years. Median time to first event was 3 vs. 30 months ( p = 0.023), respectively (Kaplan–Meier survival curve). Our assay was a better independent predictor of staying long-term on infliximab ( p = 0.056) than any other clinical or biological patients' characteristics. Conclusions: An assay-based in vitro test for functional blockade of TNFα (CD62L shedding) provides an excellent long-term (3–5 years) independent predictor of infliximab response in inflammatory bowel disease patients. Testing patients at the beginning of the infliximab maintenance phase could help therapeutic decision making to avoid complications, hospitalisation and surgeries.